Fiscal space on the eurozone periphery: The case of Spain - Jorge Uxó González; Ignacio Álvarez; Eladio Febrero (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2017)
On the one hand, every official document about fiscal policy in Spain, and most orthodox academic papers argue that Spain has no "fiscal space" and that it should apply resolute actions to assure budget consolidation. On the other hand, Spain also had the second highest unemployment rate in the Eurozone in 2015: 21% of the active population. A rapid decline in that rate would require a higher fiscal impulse to sustain higher economic growth rates. This paper addresses this dilemma, presenting two alternative scenarios for the coming years and analyzing their impact on unemployment and fiscal sustainability. The first scenario represents a firm commitment to budget consolidation, while in the second the government uses the fiscal instrument to stimulate domestic demand and ensure a GDP growth rate target. The second scenario is based on an application of an "imperfect" balanced budget multiplier, proposing a combination of discretionary increases in both public expenditure and revenue. The main conclusion is that the end of fiscal austerity is feasible and perfectly compatible with fiscal finances sustainability for Spain.
Keywords: E61; E62; 330; Fiscal Policy; Fiscal Space; Functional Finance; Balance Budget Multiplier; Spain